Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.tem.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

ATP Citrate Lyase: A New Player Linking Skeletal Muscle Metabolism and Epigenetics

Abstract: Intermediates generated in several metabolic processes are used to regulate transcription through covalent histone and DNA modifications. In Cell Reports, Das et al. show that acetyl-coenzyme A (acetyl-CoA) generated by ATP citrate lyase (ACL) is utilized to acetylate histone H3 at MyoD regulatory regions, resulting in increased MyoD expression and improved muscle regeneration after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although expression levels of the myogenic regulatory factor MyoD were essentially unchanged in the SKMiPLA 2 γKO in comparison to WT controls, markedly increased expression of Myogenin due to iPLA 2 γ loss of function in skeletal muscle is indicative of more active regenerative myogenesis in SKMiPLA 2 γKO vs. WT mice ( Figure 2 I). Furthermore, the expression level of ATP citrate lyase (ACL), a key enzyme regulating muscle cell growth/differentiation, muscle type transition, and mitochondrial function, 18 , 19 and its active (phosphorylated at Ser455) form were moderately upregulated in SKMiPLA 2 γKO mouse TA muscle likely facilitating skeletal muscle regeneration and the observed increase in fast skeletal myosin expression ( Figure 2 I).…”
Section: Resultsmentioning
confidence: 99%
“…Although expression levels of the myogenic regulatory factor MyoD were essentially unchanged in the SKMiPLA 2 γKO in comparison to WT controls, markedly increased expression of Myogenin due to iPLA 2 γ loss of function in skeletal muscle is indicative of more active regenerative myogenesis in SKMiPLA 2 γKO vs. WT mice ( Figure 2 I). Furthermore, the expression level of ATP citrate lyase (ACL), a key enzyme regulating muscle cell growth/differentiation, muscle type transition, and mitochondrial function, 18 , 19 and its active (phosphorylated at Ser455) form were moderately upregulated in SKMiPLA 2 γKO mouse TA muscle likely facilitating skeletal muscle regeneration and the observed increase in fast skeletal myosin expression ( Figure 2 I).…”
Section: Resultsmentioning
confidence: 99%
“…The acetyl‐CoA produced by this enzyme is used as a substrate by the histone acetyltransferases (HAT) to modulate acetylation of histones. Additionally, acetyl‐CoA can be used for the acetylation of transcription factors, such as p65 NF‐κB (Das et al, ; H. Li & Sartorelli, ). The activity of ACLY and consequently H3K9 and H3K27 acetylation was shown to be increased in human knee OA chondrocytes.…”
Section: Oa and Epigeneticsmentioning
confidence: 99%
“…The acetyl-CoA produced by this enzyme is used as a substrate by the histone acetyltransferases (HAT) to modulate acetylation of histones. Additionally, acetyl-CoA can be used for the acetylation of transcription factors, such as p65 NF-κB (Das et al, 2017;H. Li & Sartorelli, 2018).…”
Section: Histone Modifications In Oamentioning
confidence: 99%
“… 14 Inhibition of ACLY can delay the occurrence of tumors. 15 , 16 To date, a large number of studies have been carried out to confirm the importance of ACLY in alcoholic fatty liver, coronary atherosclerosis, tumors, and other diseases. For example, a previous study showed that the consumption of fish oil reduced blood lipids and restrained the activity of ACLY by downregulating SREBP1 in humans.…”
Section: Introductionmentioning
confidence: 99%